Synaptic vesicle characterization of iPSC-derived dopaminergic neurons provides insight into distinct secretory vesicle pools - Kenshiro Fujise; Jaya Mishra; Martin Shaun Rosenfeld; Nisha Mohd Rafiq (npj Parkinson's Disease)
Abstract The dysfunction of dopaminergic (DA) neurons is central to Parkinson’s disease. Distinct synaptic vesicle (SV) populations, differing in neurotransmitter content (dopamine vs. glutamate), may vary due to differences in trafficking and exocytosis. However, the structural organization of these vesicles remains unclear. In this study, we examined axonal varicosities in human iPSC-derived DA and glutamatergic neurons (i3Neurons). i3Neurons primarily contained small, clear SVs (40–50 nm), whereas DA neurons contained larger, pleiomorphic vesicles including dense core and empty vesicles, in addition to the classical SVs. VMAT2-positive vesicles in DA neurons, which load dopamine, were spatially segregated from VGLUT1/2-positive vesicles in an SV-like reconstitution system. These vesicles also colocalized with SV markers (e.g., VAMP2, SV2C), and can be clustered by synapsin. Moreover, DA axonal terminals in mouse striata showed similar vesicle pool diversity. These findings reveal structural differences in DA neurons’ vesicles, highlighting iPSC-derived neurons as effective models for studying presynaptic structures.